Penerapan Metode Analytical Hierarchy Process pada Sistem Pendukung Keputusan Seleksi Penerimaan Karyawan - Sigit Maulana; Heri Haerudin (CV. Multi Kreasi Media, 2022)
The selection of effective and efficient employee recruitment is one of the important stages to help employee productivity at work. But the management of a company has problems in selecting employees. As in PT Inti Cakrawala Citra, especially decision makers who have problems determining the candidate with the best results and according to the existing criteria in determining this employee recruitment selection decision, some are done subjectively. From these existing constraints, a solution was made, namely a decision support system that can facilitate management in the selection of this employee acceptance. One method that can be used in this decision support system is the Analytical Hierarchy Process (AHP) method where this method is a method that can solve not structured or semi-structured problems. This system is made using the PHP programming language, the Extreme Programming system development method, and the design using the Unified Modeling Language. Implementation was carried out on five samples of test and interview results and using 6 criteria such as Intelligence, Work Attitude, Personality, Appearance, Communication, and Experience of the candidates, then obtained the required ranking results. With the existence of a decision support system using the AHP method, it is hoped that it can be used as a complement in the selection of employee recruitment because it can help facilitate the selection of employee recruitment while reducing subjective assessments.